Development of An Instrument for Measuring the Student Learning Outcomes: A Content Validation Process - Handage, Sushant; Chander, Mahesh (Indian Journal of Extension Education, 2021)
Content validation is a critical phase in scale development. It provides the preliminary evidence on construct validity of an instrument. The content validation process followed in developing a scale designed to measure the student learning gains is explained in detail. Content validation involves two stages, identification of the content domain and item generation, and determining the content validity. A mixed deductive-inductive method was adopted for item generation. The content validity was assessed in two rounds, in the first round the Content Validity Ratio (CVR) was computed and the items with CVR critical value of 0.407 or above were accepted and subjected to computation of Content Validity Index (CVI) in the second round. Modified kappa values were determined to overcome the chance factor. The Item-Content Validity Index (I-CVI) values were computed to finalise the items in the final scale while the Scale-Content Validity Index (S-CVI) was determined to check for stability of each dimension as well as the scale as a whole. The CVI value above 0.78 was considered fit for the scale.
Keywords: Content validation; Content validity index; Content validity ratio; Scale development; Item generation for scale